Validation of an instrument for the application of principled bioethical principles in clinical research protocols - Bustos Saldaña, Rafael; en Bioética de América Latina, Grupo de Investigación (Acta Bioethica, 2024)
The aim of this article is to report on the validation of an instrument on the application of principialist bioethical principles in each of the elements of clinical research protocols. To this end, a 173-item instrument was evaluated using the Delphi method, with the collaboration of 12 Latin American experts in research bioethics. The instrument underwent two rounds of revision. In the end there were only 171 items, in which the bioethical principles were applied 208 times, of which 87 (41.82%) belonged to Beneficence, 63 (30.29%) to Non-Maleficence, 36 (17.31%) to Justice and 22 (10.58%) to Autonomy. Regarding the congruence of the principles in general with respect to the variables of the elements of the clinical research protocol, it was found on 189 (90.87% CI 95% 86.10 to 94.41) occasions, K=0.98 (0.01), p=<0.0001. It is concluded that the validated instrument gives us the option of applying the bioethical principles of the principialist current to each of the elements of the clinical research protocols.